Desenvolvimento de equipamento de eletroforese capilar com detecção por condutividade sem contato para a separação de íons inorgânicos - Spengler, Cristiane (2009)
This work describes the development and evaluation of a home-made capillary electrophoresis (CE) system based on the capacitively coupled contactless conductivity detection (C4D) for the application in capillary zone electrophoresis (CZE). The C4D detection is based on prototypes previously described in the literature. The equipment constructed has a hydrodynamic injection system (gravity), a temperature control system based on the heating of the system and it is equipped with two carousels for the sample changing. The electrophoretic system developed in this work has a high automation degree in relation to other existing CE systems. All the components of the CE system are operated by a computer interface, including the sample changers that allow the manipulation of solutions in a fully automated way. The control of the components of the CE system and the data acquisition were made by using a software, which was developed in a Delphi 7.0 language. After the construction and configuration of the CE system, the performance was initially evaluated by applying some methods previously described in the literature for the separation of Na(I), K(I), Ca(II) and Mg(II). The results are in agreement with the literature and show the proper performance of the home-made CE C4D system. The developed system was used for the simultaneous determination of the metallic species Zn(II), Cr(III), Pb(II), Cd(II), Co(II), Cu(II), Ni(II) and Tl(I) in different samples. The separation of 8 cations was investigated by using working electrolytes containing 2-[N-morpholino]ethanesulfonic acid (MES) and histidine (His) at different compositions. The use of complexing agents and an organic solvents as additives was also evaluated. The optimized conditions enabled the determination of 8 cations in a single run after 15 minutes using a solution containing 20 mmol L−1 MES/His (pH 5.0) and 5% MeOH (v/v) as working electrolyte, 10 kV as separation potential and the C4D detector operating at 600 kHz and 2 Vpp. The constructed CE-C4D system was shown to be very reproducible for electrophoretic analysis of metallic cations, with relative standard deviations (RSD) for the migration times of all the studied cations ranging from 2.6 to 9.2%. The detection limits calculated for the 8 cations ranged from 1.69 to 22.17 μmol L−1, which allows the application of the methodology for determinations in real samples using the developed electrophoretic system.